P074: Emergency department utilization and outcomes for patients with early pregnancy complications. (May 2020) - Glicksman, R.; Little, D.; Thompson, C.; McLeod, S.; Varner, C.
Abstract : Introduction: Affecting roughly 1 in 5 pregnancies, early pregnancy loss is a common experience for reproductive-aged women. In Canada, most women do not establish care with an obstetrical provider until the second trimester of pregnancy. Consequently, pregnant patients experiencing symptoms of early pregnancy loss frequently access care in the emergency department (ED). The objective of this study was to describe the resource utilization and outcomes of women presenting to two Ontario EDs for early pregnancy loss or threatened early pregnancy loss. Methods: This was a retrospective cohort study of pregnant (≤20 weeks), adult (≥18 years) women in two EDs (one community hospital with 110, 000 annual ED visits; one academic hospital with 65, 000 annual ED visits) between January 2010 and December 2017. Patients were identified by diagnostic codes indicating early pregnancy loss or threatened early pregnancy loss. Results: A total of 16, 091 patients were included, with a mean (SD) age of 32.8 (5.6) years. Patients had a total of 22, 410 ED visits for early pregnancy complications, accounting for 1.6% of the EDs' combined visits during the study period. Threatened abortion (n = 11, 265, 50.3%) was the most common ED diagnosis, followed by spontaneous abortion (n = 5, 652, 25.2%), ectopic pregnancy (n = 3, 242, 14.5%), missed abortion (n = 1, 541, 6.9%), and other diagnoses (n = 710, 3.2%). 8, 000 (44.8%) patients had a radiologist-interpreted ultrasound performed during the initial ED visit. Median (IQR) ED length of stay was 3.4 (2.3 to 5.1) hours. There were 4, 561 (25.6%) return ED visits within 30 days, of which 2, 317 (50.8%) occurred less than 24 hours of index visit, and 481 (10.6%) were for scheduled, next day ultrasound. The total number of hospital admissions was 1, 793 (8.0%), and the majority were for ectopic pregnancy (n = 1, 052, 58.7%). Of admitted patients, 1, 320 (73.6%) underwent surgical interventions related to early pregnancy. There were 474 (10.4%) patients admitted to hospital during return ED visits. Conclusion: Pregnant patients experiencing symptoms of early pregnancy loss in the ED frequently had radiologist-interpreted US and low rates of hospital admission, yet had high rates of return ED visits. This study highlights the heavy reliance on Ontario EDs to care for patients experiencing complications of early pregnancy.